PEMANFAATAN LIMBAH KARDUS UNTUK PERANCANGAN LAMPU HIAS BERGAYA SCANDINAVIAN - Raihanah, Salwa Nawa; Nurhidayat, Martiyadi; Pujiraharjo, Yoga (eProceedings of Art & Design, 2024)
Cardboard waste, which is produced from industry and daily activities, can be processed into paper as the main material for Scandinavian-style decorative lamps, in addition to being processed into handicrafts. This time, the design produces Scandinavian decorative lamps using corrugated cardboard waste, aiming to reduce industrial cardboard waste. The inductive method is used to analyze data from field facts, while the SCAMPER method is applied to develop useful products. This decorative lamp is ideal to place in the living room as decoration and lighting. Key words: waste, cardboard, industry.